On (h, k, µ, ν)-trichotomy of evolution operators in Banach spaces - MEGAN, Mihail; CEAUȘU, Traian; CRAI (TERLEA), Violeta (Studia Universitatis Babeș-Bolyai Mathematica, 2019)
The paper considers some concepts of trichotomy with different growth rates for evolution operators in Banach spaces. Connections between these concepts and characterizations in terms of Lyapunov- type norms are given. Mathematics Subject Classification (2010): 34D09.